Variation in use of non-surgical treatments among osteoarthritis patients in orthopaedic practice in the Netherlands - Hofstede, Stefanie N (BMJ Open, 2015)
OBJECTIVES: National and international evidence-based guidelines for hip and knee osteoarthritis (OA) recommend to start with non-surgical treatments, followed by surgical intervention if a patient does not respond sufficiently to non-surgical treatments, but there are indications that these are not optimally used. The aim of this study was to assess the extent to which all recommended non-surgical treatments were used by patients with hip or knee OA who receive(d) a total hip or knee replacement, as reported by patients and orthopaedic surgeons. SETTING: We performed two cross-sectional internet-based surveys among patients and orthopaedic surgeons throughout the Netherlands. PARTICIPANTS: 195 OA patients either have undergone total knee arthroplasty or total hip arthroplasty no longer than 12 months ago or being on the waiting list for surgery with a confirmed date within 3 months and 482 orthopaedic surgeons were invited to participate. PRIMARY AND SECONDARY OUTCOME MEASURES: The use of recommended non-surgical treatments including education about OA/treatment options, lifestyle advice, dietary therapy, physical therapy, acetaminophen, NSAIDs and glucocorticoid injections. RESULTS: 174 OA patients (93%) and 172 orthopaedic surgeons (36%) completed the surveys. Most recommended non-surgical treatments were given to the majority of patients (eg, 80% education about OA, 73% physical therapy, 72% acetaminophen, 80% NSAIDs). However, only 6% of patients and 10% of orthopaedic surgeons reported using a combination of all recommended treatments. Dietary therapy was used least frequently. Only 11% of overweight and 30% of obese participants reported having received dietary therapy and 28% of orthopaedic surgeons reported to prescribe dietary therapy to overweight patients. CONCLUSIONS: While most recommended non-surgical treatments were used frequently as single therapy, the combination is used in only a small percentage of OA patients. Especially, use of dietary therapy may be improved to help patients manage their symptoms, and potentially delay the need for joint arthroplasty.